1997
DOI: 10.1038/bjc.1997.130
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemias and cancers following iodine-131 administration for thyroid cancer

Abstract: Summary We studied 1771 patients treated for a thyroid cancer in two institutions. None of these patients had been treated with external radiotherapy and 1497 had received 1311. The average 1311 cumulative activity administered was 7.2 GBq, and the estimated average dose was 0.34 Sv to the bone marrow and 0.80. Sv to the whole body. After a mean follow-up of 10 years, no case of leukaemia was observed, compared with 2.5 expected according to the coefficients derived from Japanese atomic bomb survivors (P = 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 7 publications
0
50
0
3
Order By: Relevance
“…The excess of colorectal cancer was previously evidenced only in the French cohort (de Vathaire et al, 1997), and the excess of salivary gland cancer was found in the Swedish (Hall et al, 1991) and Italian (Dottorini et al, 1995) cohorts. In contrast, the excess of bone and soft-tissue cancers following 131 I administration has not been previously reported.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The excess of colorectal cancer was previously evidenced only in the French cohort (de Vathaire et al, 1997), and the excess of salivary gland cancer was found in the Swedish (Hall et al, 1991) and Italian (Dottorini et al, 1995) cohorts. In contrast, the excess of bone and soft-tissue cancers following 131 I administration has not been previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…Patients with a malignancy prior to thyroid cancer, with a second malignancy within the first 2 years of follow-up, or dying within 2 years of diagnosis were excluded. The treatment modalities in each cohort have been described previously (Hall et al, 1991;Dottorini et al, 1995;de Vathaire et al, 1997).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Furthermore, in several reported instances, posttreatment WBS has revealed mediastinal 131 I activity that, on subsequent surgical exploration, was found to be attributable to physiologic enlargement of the thymus. 5,16 -20 Without appropriate guidelines, it is difficult to obtain a consensus regarding diagnostic and therapeutic strategies for patients with mediastinal uptake of 131 I.…”
mentioning
confidence: 99%
“…Also, high doses of radioactive iodine have been linked to an increased risk of leukaemias as well as bone, soft tissue, colorectal, and salivary gland cancers. 12 Radiation induced pulmonary fibrosis in patients with pulmonary metastases after repeated I-131 doses is also a potential risk, albeit rarely reported. In addition to thyroidectomy and I-131 treatment, studies also support the use of external beam radiation therapy (EBRT) for locoregional control of inoperable metastases.…”
mentioning
confidence: 99%